A Critical Review on the Book Case Studies of Organizational Behavior Management - Karim Esgandari; Shadi Orafaye Jamshidi; Elmira Shakeri; Sheida Orafaye Jamshidi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Due to the need to establish strong links between industry and academia to use scientific theories in industry, the use of case study in the management of organizational behavior is necessary. The purpose of this paper is to review and critique the book Case Studies of Organizational Behavior Management. The method of evaluation and critique of this work is citation-analytical and in accordance with the model proposed by the Council for the Study of Humanities Texts and Books in the framework of general introduction, form and content study of the work. In general, in terms of the form of the work, the form quality of the work is good, despite these formal weaknesses of the work are: not using a specific symbol of management behavior in the design on the cover of the book, not using tables, charts and the bug is inside the text. In terms of content, the use of case study method in managing organizational behavior is one of the strengths of the effect. However, the work suffers from lack of logical order and content coherence, content inaccuracy, and content defects. In general, the analysis of the content of scientific and academic books can provide their possible strengths and weaknesses for the possible modification and change of content and form, in accordance with the set goals and scientific principles to the planners and authors of academic books.